2021
DOI: 10.3390/su13084264
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Driver Assistant Systems Focused on Pedestrians’ Safety: A User Experience Approach

Abstract: Globally, pedestrians represent 23% of all road deaths. Many solutions to protect pedestrians are proposed; in this paper, we focus on technical solutions of the ADAS–Advanced Driver Assistance Systems–type. Concerning the interaction between drivers and pedestrians, we want to have a closer look at two aspects: how to protect pedestrians with the help of vehicle technology, and how pedestrians–but also car drivers–perceive and accept such technology. The aim of the present study was to analyze and describe th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Digital media system is an information carrier mode with the functions of recording, generation, dissemination, processing, and intelligent acquisition, specifically including digital animation, text information, communication network, and other diversified media forms [5,6]. The application of computer VR technology in the design of digital media system can enable the cross-border integration and development of information expression, which is conducive to further optimizing the design of digital media system and further strengthening the sense of user experience.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Digital media system is an information carrier mode with the functions of recording, generation, dissemination, processing, and intelligent acquisition, specifically including digital animation, text information, communication network, and other diversified media forms [5,6]. The application of computer VR technology in the design of digital media system can enable the cross-border integration and development of information expression, which is conducive to further optimizing the design of digital media system and further strengthening the sense of user experience.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of quantity (i.e., current volume of scientific production), it should be noted that there is still a small number of studies that analyze this specific topic, even though their overall quality has been found reasonably well after applying the selected evaluation methods. Also, it is worth mentioning that, although there is a relatively large number of articles evaluating ADAS devices on vulnerable groups, these are more focused on pedestrians or motorcyclists ( 71 , 72 ). One of the inclusion criteria of the present review is that the selected research should specifically include results on cyclists, which reduces the number of potentially selectable articles, but helps to match the findings to the characteristics of this road group.…”
Section: Discussionmentioning
confidence: 99%